Periodically poled aluminum scandium nitride bulk acoustic wave resonators and filters for communications in the 6G era - Izhar; M. M. A. Fiagbenu; S. Yao; X. Du; P. Musavigharavi; Y. Deng; J. Leathersich; C. Moe; A. Kochhar; E. A. Stach; R. Vetury; R. H. Olsson (Microsystems & Nanoengineering)
Abstract Bulk Acoustic Wave (BAW) filters find applications in radio frequency (RF) communication systems for Wi-Fi, 3G, 4G, and 5G networks. In the beyond-5G (potential 6G) era, high-frequency bands (>8 GHz) are expected to require resonators with high-quality factor (Q) and electromechanical coupling ( $${k}_{t}^{2}$$ k t 2 ) to form filters with low insertion loss and high selectivity. However, both the Q and $${k}_{t}^{2}$$ k t 2 of resonator devices formed in traditional uniform polarization piezoelectric films of aluminum nitride (AlN) and aluminum scandium nitride (AlScN) decrease when scaled beyond 8 GHz. In this work, we utilized 4-layer AlScN periodically poled piezoelectric films (P3F) to construct high-frequency (~17–18 GHz) resonators and filters. The resonator performance is studied over a range of device geometries, with the best resonator achieving a $${k}_{t}^{2}$$ k t 2 of 11.8% and a $${Q}_{{\rm {p}}}$$ Q p of 236.6 at the parallel resonance frequency ( $${f}_{{\rm {p}}}$$ f p ) of 17.9 GHz. These resulting figures-of-merit are ( $${{{\rm {FoM}}}}_{1}={{k}_{t}^{2}Q}_{{\rm {p}}}$$ FoM 1 = k t 2 Q p and $${{{\rm {FoM}}}}_{2}={f}_{{\rm {p}}}{{{\rm {FoM}}}}_{1}{× }{10}^{-9}$$ FoM 2 = f p FoM 1 × 10 − 9 ) 27.9 and 500, respectively. These and the $${k}_{t}^{2}$$ k t 2 are significantly higher than previously reported AlN/AlScN-based resonators operating at similar frequencies. Fabricated 3-element and 6-element filters formed from these resonators demonstrated low insertion losses (IL) of 1.86 and 3.25 dB, and −3 dB bandwidths (BW) of 680 MHz (fractional BW of 3.9%) and 590 MHz (fractional BW of 3.3%) at a ~17.4 GHz center frequency. The 3-element and 6-element filters achieved excellent linearity with in-band input third-order intercept point (IIP3) values of +36 and +40 dBm, respectively, which are significantly higher than previously reported acoustic filters operating at similar frequencies.